The Meaning of Spirituality in People Living with HIV/AIDS Using the Calista Roy Theoretical Approach - Sugiyanto; Bestfy Anitasari (Universitas Ahmad Dahlan, 2026)
Spirituality is a core dimension of human life in both health and illness and may influence coping and healing, particularly among people living with HIV/AIDS. This qualitative phenomenological study involved four participants who provided written informed consent and shared their lived spiritual experiences of prayer. Data were collected through in-depth interviews supported by an interview guide, field notes, and document review, and were analyzed using Colaizzi’s method (1978) with the assistance of QSR NVivo (version 10.0). Five themes emerged: (1) grief responses following diagnosis, (2) family support, (3) meanings attributed to HIV/AIDS, (4) practices for drawing closer to God, and (5) the perceived essence and effects of prayer. These findings highlight the importance of integrating culturally sensitive spiritual care into routine HIV services. Nurses should conduct early, respectful spiritual assessment after diagnosis, facilitate patients’ preferred spiritual practices in a private and nonjudgmental manner, and engage family members when appropriate and with consent—as key sources of emotional and spiritual support. Health facilities are encouraged to provide staff training and clear referral pathways to spiritual resources while safeguarding confidentiality. Further research with more diverse participants is recommended to enhance transferability and inform the development of structured spiritual care protocols.